Thrombogenicity and Antithrombotic Strategies in Structural Heart Interventions and Nonaortic Cardiac Device Therapy—Current Evidence and Practice - Geisler, Tobias; Jorbenadze, Rezo; Popov, Aron-Frederik; Mueller, Karin L.; Rath, Dominik; Droppa, Michal; Schreieck, Juergen; Seizer, Peter; Storey, Robert F.; Kristensen, Steen D.; Rubboli, Andrea; Gorog, Diana; Aradi, Daniel; Sibbing, Dirk; Huber, Kurt; Gawaz, Meinrad; Ten Berg, Jur (Thrombosis and Haemostasis, 2019)
As the number of, and the indications for, structural heart interventions are increasing worldwide, the optimal secondary prevention to reduce device thrombosis is becoming more important. To date, most of the recommendations are empiric. The current review discusses mechanisms behind device-related thrombosis, the available evidence with regard to antithrombotic regimen after cardiac device implantation, as well as providing an algorithm for identification of risk factors for device thrombogenicity and for management of device thrombosis after implantation of patent foramen ovale and left atrial appendage occluders, MitraClips/transcatheter mitral valve replacement, pacemaker leads, and left ventricular assist devices. Of note, the topic of antithrombotic therapy and thrombogenicity of prostheses in aortic position (transcatheter aortic valve replacement, surgical, mechanical, and bioprostheses) is not part of the present article and is discussed in detail in other contemporary focused articles.
Keywords: patent foramen ovale; left atrial appendage; MitraClip; left ventricular assist device; device-related thrombosis